2018
DOI: 10.1186/s12913-018-2858-7
|View full text |Cite
|
Sign up to set email alerts
|

General service and child immunization-specific readiness assessment of healthcare facilities in two selected divisions in Bangladesh

Abstract: BackgroundService readiness of health facilities is an integral part of providing comprehensive quality healthcare to the community. Comprehensive assessment of general and service-specific (i.e. child immunization) readiness will help to identify the bottlenecks in healthcare service delivery and gaps in equitable service provision. Assessing healthcare facilities readiness also helps in optimal policymaking and resource allocation.MethodsA health facility survey was conducted between March 2015 and December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 11 publications
(6 reference statements)
5
19
2
2
Order By: Relevance
“…These results concur with Shawon et al (2018) who reported that in Bangladesh, facilities at all levels had lowest scores for diagnostic capacity. Another study conducted in India reported absence of diagnostics for routine blood, urine and stool examination especially in Empowered Action Group states such as Assam where only 20% primary health centers had basic laboratory facilities (Ninama et.…”
Section: Creating Vulnerability Indexsupporting
confidence: 92%
“…These results concur with Shawon et al (2018) who reported that in Bangladesh, facilities at all levels had lowest scores for diagnostic capacity. Another study conducted in India reported absence of diagnostics for routine blood, urine and stool examination especially in Empowered Action Group states such as Assam where only 20% primary health centers had basic laboratory facilities (Ninama et.…”
Section: Creating Vulnerability Indexsupporting
confidence: 92%
“…The study was focused on two divisions with different levels of vaccination coverage: Sylhet (low coverage at 61.1%) and Rajshahi (high coverage at 83.6%) [13]. In each division, we selected a district and a city corporation, representative of rural and urban settings.…”
Section: Study Population and Sitesmentioning
confidence: 99%
“…The study was focused on two divisions with different levels of vaccination coverage: Sylhet (low coverage at 61.1%) and Rajshahi (high coverage at 83.6%) [14]. In each division, we selected a district (Maulvibazar and Natore districts) and a city corporation (Sylhet and Rajshahi city corporations), representative of rural and urban settings.…”
Section: Study Population and Sitesmentioning
confidence: 99%